2016
DOI: 10.1080/0284186x.2016.1185148
|View full text |Cite
|
Sign up to set email alerts
|

Trends in all-cause five-year mortality after head and neck cancers diagnosed over a period of 33 years. Focus on estimated degree of association with human papillomavirus

Abstract: Results: All-cause five-year mortality after HNSCC has decreased over time. The greatest decrease was seen in the last decade (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) among patients with HNSCC at sites estimated to be strongly associated with HPV, i.e. the base of the tongue and the tonsils, where a 28% decrease per five years (e.g. HR base of tongue/tonsils ¼0.72; 95% CI 0.64-0.81) was observed. When examining sex-and age-specific time trends, the decrease in mortality was most prono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
(44 reference statements)
1
21
0
Order By: Relevance
“…11,12 Racial disparities have also been described in patients with HNC. 22,23 Generalized competing event (GCE) modeling is a useful and relatively novel method for analyzing effects of treatment and risk factors on outcomes. Some studies have demonstrated no difference in survival between women and men, 11,[19][20][21] whereas other studies have found differences in survival.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Racial disparities have also been described in patients with HNC. 22,23 Generalized competing event (GCE) modeling is a useful and relatively novel method for analyzing effects of treatment and risk factors on outcomes. Some studies have demonstrated no difference in survival between women and men, 11,[19][20][21] whereas other studies have found differences in survival.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Choi et al 11 reported that women had better survival, whereas others found that outcomes for men improved over time. 22,23 Generalized competing event (GCE) modeling is a useful and relatively novel method for analyzing effects of treatment and risk factors on outcomes. 21,24,25 This approach has been validated for several cancers, including head and neck, endometrial, prostate, and breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Head and neck cancer squamous cell carcinomas (HNSCC) show a heterogeneous response to radiochemotherapy with loco-regional control and 5-year overall survival ranging from below 50% to 80% [1][2][3][4]. Few biomarkers related to tumor response to a therapy are already available for this tumor entity, for example: human papilloma virus infection [1][2], overexpression of epidermal growth factor receptor [5], tumor hypoxia or overexpression of cyclin D1 [6].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, individual‐level data on the clinical HPV status of the HNC cases was not available. Instead, we categorized the cases by topography into groups of anticipated degree of HPV‐association based on the available literature assessing HPV prevalence of different HNC sites . HPV is fully recognized as an etiological factor in oropharyngeal cancer, especially in cancer of the base of tongue and palatine tonsils with a reported HPV prevalence of more than 50% .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we categorized the cases by topography into groups of anticipated degree of HPVassociation based on the available literature assessing HPV prevalence of different HNC sites. 9,42,43 HPV is fully recognized as an etiological factor in oropharyngeal cancer, especially in cancer of the base of tongue and palatine tonsils with a reported HPV prevalence of more than 50%. 18,42 The HPV prevalence in oral and laryngeal cancer is lower (0-20%) 9,42 and the role of HPV in these cases is therefore more questionable.…”
Section: Discussionmentioning
confidence: 99%